Motivasi Pengrajin Industri Rumah Tangga dalam Menabung Di Bank di Kecamatan Amuntai Tengah Kabupaten Hulu Sungai Utara - Rum Van Royensyah; Yunita Yunita (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2017)
This study aims to determine the level of factors that influence the motivation of craftsmen, the level of motivation of craftsmen and the relationship between the level of factors that influence the motivation of home industry craftsmen in saving money in the bank. This research was conducted in Amuntai Tengah District, Hulu Sungai Utara Regency. Based on the results of the study stating that the F test together the factors that influence motivation significantly influence the motivation of home industry craftsmen in saving at the bank, while the t test partially only the availability of production facilities that have a significant effect on the motivation of craftsmen in saving at bank. While the relationship of factors that influence the motivation of craftsmen is the education level variable and the availability of production facilities variables that have a significant relationship because the value of rs is 0.254 with sig 0.012 <0.05 and -0, 274 with sig 0.0007 <0.05 . In the age variable, building area, income, availability of saving places and market guarantees there is no significant relationship because the sig value of each variable is> 0.05.